Serializing protestantism: the missionary Miscellany and the Arabic press in 1850s Beirut. Issue 1 (1st January 2022) - Edwards, Anthony
ABSTRACT: This article explores the connections between two distinct publishing enterprises in 1850s Beirut to put into relief how American missionaries and learned Syrians in tandem shaped the early Arabic press industry. It examines Syrian journalistic ambitions, a missionary foray into serialized print, and the material practices of early Arabic publishing. Section one provides the first detailed history of the Miscellany (1851–1856), a series of religious pamphlets produced by the missionaries known in Arabic as Majmuʿ Fawayid (A Collection of Useful Knowledge). Through a material analysis of the publication, it also expands on the extent archival record and discusses developments to the format of the serial. Section two advances an updated establishment story of Hadiqat al-Akhbar (1858–1907), the first Arabic newspaper in the city. It spotlights a disremembered leader of the journalistic enterprise, Antonius Ameuney (1821–1881), and pinpoints the origins of the newspaper to a group of Syrians assembled at the forgotten Médawar Literary Circle. The entangled history of the Arabic press shows how foreigners and locals worked simultaneously to realize different visions for a serial publication in Beirut in the early days of the Arab Nahḍa (Renaissance).